As cotas por sexo para a competição legislativa: o caso brasileiro em comparação com experiências internacionais - Araújo Clara (Dados: Revista de Ciências Sociais, 2001)
This article analyzes a specific type of affirmative action focusing on women, i.e., a quota policy for legislative candidacies, taking the Brazilian experience as the empirical base. Using a comparison with similar approaches to this policy and their results in different countries, the paper evaluates the impacts on legislative elections in Brazil since 1996, when such quotas were adopted in the country for the first time. After concluding that the policy has had little impact on the election pattern of women candidates in Brazil (unlike the experience in other countries), the article discusses possible explanatory factors.